Determinants of Lending Interest Rates of Nepalese Commercial Banks - Bhattarai, Yuga Raj (Economic Journal of Development Issues, 2017)
The aim of this study is to investigate the determinants of lending rate of Nepalese commercial banks. The analysis of data was based on a sample of 6 commercial banks observed over the period 6 years (2010 to 2015). The models used in the study were: pooled OLS model, fixed effects model and random effects model. This study has used ‘lending rate’ as dependent variable, while the explanatory variables are: operating cost to total assets ratio, deposit interest rate, profitability (ROA) and default risk. The estimated results of these three regression models reveal that operating costs to total assets ratio, profitability (ROA) and default risk have significant positive impact on the commercial bank lending rate. However, deposit rate has negligible impact on lending interest rate. Thus, this study concludes that the major determinants of commercial banks’ lending rate are: operating costs to total assets ratio, profitability (ROA) and default risk in Nepalese perspectives.Economic Journal of Development Issues Vol. 19 & 20 No. 1-2 (2015) Combined Issue, Page: 39-59